Thibbun Nabawi: History, Culture, and Adaptation of Cupping Therapy in the Digital Age - Susanto, Dwi (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This research aims to explore Thibbun Nabawi, specifically cupping therapy, within the contexts of history, culture, and its adaptation in the digital age. Thibbun Nabawi, as a system of medicine originating from the teachings of Prophet Muhammad SAW, possesses extensive and profound historical and cultural roots, encompassing practices passed down through generations. Cupping therapy, as one of its practices, has traversed various civilizations and cultures, demonstrating its relevance in a global context. This study traces the history and culture of cupping therapy, and analyzes how this practice adapts to technological developments in the digital era, including the use of digital platforms for education and services. An interdisciplinary approach, integrating history, culture, religion, and technology, is employed to comprehensively understand the phenomenon of cupping therapy. The research findings indicate that cupping therapy has a strong historical foundation in both Islamic tradition and global culture, with evidence of its practices found in various historical records. These findings also reveal a significant transformation in the practice of cupping therapy in the digital age, marked by the emergence of online platforms and health applications that facilitate access to information and services, and enable cupping practices to reach a wider audience. The implication of this research is the need to develop clear standards and regulations for cupping therapy practices in the digital era, to ensure its safety and effectiveness in maintaining its integrity amidst developments in technology and information.